(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article analyzes on a scientific basis the systemic and qualitatively important changes that have occurred in the terminology of the Uzbek language in the period of independence. In the post-independence period, the main research object is considered the changes in the attitude to the state language, language policy, terminological reforms, revival and activation of national terms. The article also analyzes the development of sectoral terminology, linguistic mechanisms of term formation, processes of normation and standardization. The results of the article serve to assess the modern state of Uzbek terminology and to form further directions of development.